DNA display of fragment pairs as a tool for the discovery of novel biologically active small molecules. Issue 1 (6th October 2014) - Daguer, J.-P.; Zambaldo, C.; Ciobanu, M.; Morieux, P.; Barluenga, S.; Winssinger, N.
Abstract : A focused library for Hsp70 was prepared from fragments identified from an array combinatorially pairing two libraries of small molecule fragments. Screening of the focus library yielded high affinity ligand to Hsp70. Abstract : Fragment-based lead discovery has proven to be a powerful method in the drug discovery process. The combinatorial output that is accessible by combining fragments is very attractive; however, identifying fragment pairs that bind synergistically and linking them productively can be challenging. Several technologies have now been established to prepare and screen nucleic acid-encoded libraries (ssDNA, dsDNA, PNA), and it has been shown that pairs of molecules combined by hybridization can bind synergistically to a target. Herein we apply this concept to combinatorially pair two libraries of small molecule fragments, use the fittest fragments supplemented with closely related analogs to build a focused library covalently linking the fragments with different spacers, and apply this strategy to the discovery of a potent ligand for Hsp70.